The Centre - Manazir Siddiqi, Ayesha (Gillian Flynn Books, a Zando imprint, 2023)
"Anisa Ellahi dreams of being a translator of "great works of literature," but mostly spends her days subtitling Bollywood movies and living off her parents' generous allowance. Adding to her growing sense of inadequacy, her mediocre white boyfriend, Adam, has successfully leveraged his savant-level aptitude for languages into an enviable career. But when Adam learns to speak Urdu practically overnight, Anisa forces him to reveal his secret. Adam begrudgingly tells her about The Centre, an elite, invite-only program that guarantees complete fluency in any language, in just ten days. This sounds, to Anisa, like a step toward the life she's always wanted. Stripped of her belongings and all contact with the outside world, she enrolls and undergoes The Centre's strange and rigorous processes. But as Anisa enmeshes herself further within the organization, seduced by all that it's made possible, she soon realizes the hidden cost of its services"--